Slowing Down of So-called Chaotic States: “Freezing” the Initial State - Belger, M.; Nigris, S. De; Leoncini, X. (Discontinuity, Nonlinearity, and Complexity, 2026)
The so-called chaotic states that emerge on the model of XY interacting on regular critical range networks are analyzed. Typical time scales are extracted from the time series analysis of the global magnetization. The large spectrum confirms the chaotic nature of the observable, anyhow different peaks in the spectrum allows for typical characteristic time-scales to emerge. We find that these time scales τ (N) display a critical slowing down, i.e they diverge as N →ꝏ. The scaling law is analyzed for different energy densities and the behavior τ (N) ∼ √ N is exhibited. This behavior is furthermore explained analytically using the formalism of thermodynamicequations of the motion and analyzing the eigenvalues of the adjacency matrix.